2015
DOI: 10.1016/j.nanoen.2014.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on nanogenerators

Abstract: The desire for self-powered nanosystems and wearable devices has driven wide investigation of the sustainable energy source. Harvesting energy from the ambient environment with nanogenerators becomes a viable solution with the development of low-power electronics. Different devices can face dramatically different working conditions, which may seriously restrict the application of those nanogenerators. In this review article we describe the most recent progress in the study of the environmental effect on the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(95 citation statements)
references
References 92 publications
(129 reference statements)
3
91
0
1
Order By: Relevance
“…In addition, the operation of NGs sensitively depends on external environmental conditions, such as temperature, humidity, water, gas, absorption, and radiation. It turns out that temperature has a negative effect on the electrical output performance of NGs . Piezoelectric materials will lose their permanent electric dipoles above their Curie or melting temperature .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the operation of NGs sensitively depends on external environmental conditions, such as temperature, humidity, water, gas, absorption, and radiation. It turns out that temperature has a negative effect on the electrical output performance of NGs . Piezoelectric materials will lose their permanent electric dipoles above their Curie or melting temperature .…”
Section: Discussionmentioning
confidence: 99%
“…Nature of the leaves and their dissimilar contact surface strongly affect the output performances of the energy harvesting nanogenerator. [168] Thus natural leaves integrated biodegradable Leaf-TNG would be future definition for green energy harvesting systems and would be better choice in future smart electronics world. The comparative output voltage and current values were well studied with different leaves when contacted with PMMA ( Figure 19q).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[ 26,27 ] However, it has been demonstrated that the triboelectrifi cation effect can be greatly affected by the environmental conditions, such as humidity and surface adsorption layers. [ 4,28,29 ] Thus, packaging plays a critical role for TENG toward broader practical applications especially for in vivo medical purposes and under water. Due to the presence of the mechanical triggering, packaging of TENG while preserving the ability of the moveable part to be driven by the external mechanical triggering is important for retaining and improving its performance.…”
Section: Introductionmentioning
confidence: 99%